2016
DOI: 10.1371/journal.pone.0160582
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Aversiveness of Surgical Procedure Pictures Is Modulated by Personal/Occupational Relevance

Abstract: It is well established that emotions are organized around two motivational systems: the defensive and the appetitive. Individual differences are relevant factors in emotional reactions, making them more flexible and less stereotyped. There is evidence that health professionals have lower emotional reactivity when viewing scenes of situations involving pain. The objective of this study was to investigate whether the rating of pictures of surgical procedure depends on their personal/occupational relevance. Fifty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 49 publications
2
12
1
6
Order By: Relevance
“…Nevertheless, the study showed a significant difference between the group before clinical traineeship and the group after clinical traineeship in terms of the valence. This finding is different from Paes et all results which revealed no significant difference between a group of nurses and a social group when evaluating negative images from IAPS (11).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the study showed a significant difference between the group before clinical traineeship and the group after clinical traineeship in terms of the valence. This finding is different from Paes et all results which revealed no significant difference between a group of nurses and a social group when evaluating negative images from IAPS (11).…”
Section: Discussioncontrasting
confidence: 99%
“…Convinced to the importance of these tools, several studies have been carried out, many studies from America [1,4,5,7], and other studies have been conducted in various parts of the world: In France [8,9], in Brazil [10][11][12], in Germany [13], in China [14,15], in Korea [16], in Lithuania [17], in Belgique [18] and in Iran [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The IAPS emotional categories were neutral (objects, people, animals and plants), pleasant (from low to high arousal: happy families, babies and puppies, nature scenes, sports and erotica) and unpleasant (from low to high arousal: pollution, loss, disgusting, disease, violence and mutilated bodies). The use of different IAPS pictures as backgrounds, varying in valence and arousal, served as the affective bases of comparison during the evaluation of the target pictures, thus anchoring the emotional rating scales ( 20 , 24 , 25 ) . This standard procedure provides valid between-group ratings, as previously noted ( 20 , 25 , 26 , 48 ) .…”
Section: Methodsmentioning
confidence: 99%
“…The use of different IAPS pictures as backgrounds, varying in valence and arousal, served as the affective bases of comparison during the evaluation of the target pictures, thus anchoring the emotional rating scales (20,24,25) . This standard procedure provides valid between-group ratings, as previously noted (20,25,26,48) .…”
Section: Stimulimentioning
confidence: 99%
See 1 more Smart Citation